PROGRAM KELUARGA HARAPAN (PKH) DALAM MENINGKATKAN KESEJAHTERAAN EKONOMI MASYARAKAT DI KECAMATAN SAMBAS PERSPEKTIF MAQASHID SYARIAH - Sariman Sariman; Munadi Munadi; Deni Irawan (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2022)
This study aims to analyze the concept, and the implementation of the family hope program to improve the economic welfare of the perspective of maqasid shariah in the District of Sambas Sambas Regency. This research is qualitative descriptive research that aims to describe the family hope program in concept and implementation. As for the data collection, the researcher used the method of observation, interview and documentation. Then proceed by analyzing and using the way of reduction, data presentation and conclusion. The results of this study showed that, in concept, the family hope program in the District of Sambas in perspekti Maqasid shariah, namely : in keeping religion (Hifzu din) through the relationship that the meeting of the group, in keeping with the sense (Hifzu al-aql) through access to education and changes in the pattern; in the keeping of the soul (Hifzu al-Nafs), through access to health care; in keeping descent (Hifzu al-Nasl) the custody of the health and safety of mother and child; in guarding the treasure (hifzu al - mal) through the improvement of the economic sector of the beneficiary Family Hope Program. While the implementation, the family hope program in the District of Sambas perspective of Maqasid shariah, namely in the first implementation, the determination of the target beneficiaries of the program the family hope that the women in this pregnant and lactating women in this included keeping descent, while the target toddler in the health field included into the spirit and objectives for the school-age children to continue their education this includes keeping any sense. the implementation of the second, and the socialization of the occurrence of the relationship between religious believers, it is included into the keeping of religion, in Addition, in the process of socialization and meeting the group held a sharing and discussion about education, health and economic terms is included into the keeping of sense. The implementation of the third, the distribution of assistance and evaluation program is to provide additional income for the recipient family hope program to meet the needs of the day especially for the field of education through cash assistance in the form of money.